CO Electroreduction Mechanism on Single-Atom Zn (101) Surfaces: Pathway to C2 Products - Yixin Wang; Ming Zheng; Xin Zhou; Qingjiang Pan; Mingxia Li (Molecules, 2023)
Electrocatalytic reduction of carbon dioxide (CO2RR) employs electricity to store renewable energy in the form of reduction products. The activity and selectivity of the reaction depend on the inherent properties of electrode materials. Single-atom alloys (SAAs) exhibit high atomic utilization efficiency and unique catalytic activity, making them promising alternatives to precious metal catalysts. In this study, density functional theory (DFT) was employed to predict stability and high catalytic activity of Cu/Zn (101) and Pd/Zn (101) catalysts in the electrochemical environment at the single-atom reaction site. The mechanism of C2 products (glyoxal, acetaldehyde, ethylene, and ethane) produced by electrochemical reduction on the surface was elucidated. The C-C coupling process occurs through the CO dimerization mechanism, and the formation of the *CHOCO intermediate proves beneficial, as it inhibits both HER and CO protonation. Furthermore, the synergistic effect between single atoms and Zn results in a distinct adsorption behavior of intermediates compared to traditional metals, giving SAAs unique selectivity towards the C2 mechanism. At lower voltages, the Zn (101) single-atom alloy demonstrates the most advantageous performance in generating ethane on the surface, while acetaldehyde and ethylene exhibit significant certain potential. These findings establish a theoretical foundation for the design of more efficient and selective carbon dioxide catalysts.